2001
DOI: 10.1093/brain/124.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Selective impairment of verb processing associated with pathological changes in Brodmann areas 44 and 45 in the motor neurone disease–dementia–aphasia syndrome

Abstract: We report six patients with clinically diagnosed and electrophysiologically confirmed motor neurone disease (MND), in whom communication problems were an early and dominant feature. All patients developed a progressive non-fluent aphasia culminating in some cases in complete mutism. In five cases, formal testing revealed deficits in syntactic comprehension. Comprehension and production of verbs were consistently more affected those that of nouns and this effect remained stable upon subsequent testing, despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
251
0
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 371 publications
(283 citation statements)
references
References 53 publications
23
251
0
9
Order By: Relevance
“…We found a similar pattern for lesions in the right non-dominant hemisphere. Furthermore, Bak et al [2], Bak and Hodges [3] recently reported that bilateral lesions of frontal areas, as present in motor neuron disease, can also have specific effects on the processing of action verbs. In addition, Cappa et al [10] found most pronounced deficits in fronto-temporal dementia.…”
Section: Comparison Of the Present Results With Earlier Findingsmentioning
confidence: 99%
“…We found a similar pattern for lesions in the right non-dominant hemisphere. Furthermore, Bak et al [2], Bak and Hodges [3] recently reported that bilateral lesions of frontal areas, as present in motor neuron disease, can also have specific effects on the processing of action verbs. In addition, Cappa et al [10] found most pronounced deficits in fronto-temporal dementia.…”
Section: Comparison Of the Present Results With Earlier Findingsmentioning
confidence: 99%
“…4 It should be added that several neuropsychological studies testify that frontal lesions, including those of the premotor cortex, produce deficits in the comprehension of action verbs (Bak & Hodges, 2003;Bak, O'Donovan, Xuereb, Boniface, & Hodges, 2001;Bak et al, 2006;Kemmerer & Tranel, 2000. We certainly need more research.…”
Section: Aq11 Mirror Neurons and The Social Nature Of Languagementioning
confidence: 99%
“…1 The third set of stimuli included 48 one-syllable pseudo-words, formally plausible but meaningless syllables like wug, torge and flonk. We used four different kinds of sentence frame, all along the lines of those given above, such that R.C.…”
Section: Sentence Completion: Noun/verb Contrastsmentioning
confidence: 99%
“…'s specific problems with verb production may stem from damage to part of the left midfrontal gyrus supe-rior to Broca's area, corresponding to Brodmann area 9. Lesions in this region have been linked to verb retrieval deficits in patients with stroke and neurodegenerative diseases [1,8,13], and neuroimaging studies have shown that left prefrontal/premotor cortex is recruited (along with other parts of the brain) more heavily during verb naming than noun naming [36,38]. However, the significance of this association has been controversial.…”
Section: Neuroanatomical Correlates Of Grammatical Processingmentioning
confidence: 99%